Can left atrial mechanics predict anticoagulation in cryptogenic stroke?. (25th November 2020) - Azul Freitas, A; Milner, J; Ferreira, J; Ferreira, C; Martinho, S; Almeida, J; Goncalves, V; Jorge, E; Goncalves, L
Abstract: Introduction: Ischemic stroke is a leading cause of death and disability in the Western world, frequently due to cardioembolism and atherothromboembolism. Cryptogenic strokes occur without a well-defined aetiology after a standard vascular and cardiac evaluation, and secondary prevention may include antiplatelet therapy while awaiting results of long-term cardiac monitoring. In this study, we aimed to identify echocardiographic predictors of paroxysmal atrial fibrillation (AF) latter identified in follow-up of patients with cryptogenic stroke. Methods: We retrospectively assessed all patients with cryptogenic stroke admitted in our hospital in the last 2 years. Only patients in normal sinus rhythm with a minimum of 24 hours of cardiac monitoring at admission and 24 hours Holter monitor within 6 months after discharge were included. Echocardiographic measures included left ventricle ejection fraction, left atrium (LA) volume, left and right atrium longitudinal strain, left and right ventricle longitudinal strain, E/A ratio, E/e' ratio, isovolumetric relaxation time (IVRT) and E wave deacceleration time. Echocardiographic data was assessed to determine its accuracy to identify AF. Results: The study included 32 patients with a mean age of 72±10 years and a male preponderance (87.5%). AF was identified in 12 (37.5%) patients. This group of patients had a larger indexed LA volume (44.3 vs 29.1 mL/m 2, p=0.043), a lower IVRT (87 vs 116 ms, p=0.028), and a lower LA longitudinal strain in contractile (6.7 vs 13.6%, p<0.001) and in reservoir phase (17.1 vs 23.6%, p=0.042). All other variables were not significantly different among groups, including LA longitudinal strain in conduit phase. LA longitudinal strain in contractile phase showed the best predictive power with an area under the ROC curve of 0.925 (95% CI 0.82–1 p=0.001). The cut-off value that best predicted AF was 8.17% with a sensitivity of 1 and specificity of 0.9. Conclusion: LA longitudinal strain in contractile phase is a powerful method to identify AF in cryptogenic stroke. When reduced, anticoagulation may be considered in order to prevent recurrence. Further studies are warranted to reproduce these results in larger cohorts. Funding Acknowledgement: Type of funding source: None